Lucy's Law comes into force. (2nd June 2020) - Abraham, Marc
Abstract : After years of campaigning Lucy's Law was passed in the summer of 2019, and became enforceable from April 6 2020. It ensures that puppies and kittens can only be sold in the place in which they were born, and in the presence of their mother.